Skrining Fitokimia Ekstrak Herba Serai Wangi (Cymbopogon nardus) Variasi Pelarut dan Stabilitas Lotion Repellent Nyamuk - Dwi Retno Sari; Moh Mukhlishin; Fawwaz Muhammad Fauzi (LPPM Universitas Abdurrab, 2024)
Dengue Hemorrhagic Fever (DHF) is a health problem in Indonesia. Until the 22nd week of 2024, there were 119,709 dengue cases with 777 deaths. The use of citronella (Cymbopogon nardus) repellent is done to prevent it. This study aims to determine the content of citronella extract with ethanol (polar), ethyl acetate (semi-polar), and n-hexane (non-polar) solvents as active ingredients of mosquito repellent lotion and determine the stability of the lotion. The type of this research is experimental research with true experimental design:the posttest-only control group design. Phytochemical screening was conducted to determine the saponin, flavonoid, alkaloid, phenolic, triterpenoid, and steroid content of each extract. Lotion stability is tested for 28 days by storing the lotion at room temperature. On days 0, 14, and 28, the organoleptic, homogeneity, pH, adhesion, spreadability, and emulsion type tests were carried out on the lotion. The results of phytochemical screening showed that the ethanol extract contains saponins, flavanoids, and phenolics. The ethyl acetate extract contains steroid. The n-hexane extract contains triterpenoid and steroid. The results of the stability test showed that all preparations met the requirements of the organoleptic test, homogeneity test, pH test, adhesion test, and emulsion type test which are good and stable. But it does not meet the requirements of a good spreadability test.